EXPLORING INTERSECTIONALITY: THE LEGAL CHALLENGES FACED BY INDIGENOUS WOMEN IN PALM OIL LAND CONFLICTS - Aga Natalis; Shannon Lorelei Wibowo; Ester Elisabeth Aspin N; Marzellina Hardiyanti; Aju Putrijanti (Fakultas Hukum, Universitas Diponegoro, 2025)
This study explores the dual challenges faced by indigenous women in palm oil land conflicts through an intersectionality framework to understand their unique oppression. In Indonesia, the palm oil industry’s expansion has exacerbated gender-based, ethnic, economic, and ecological injustices faced by these women. Indigenous women are often excluded from decision-making processes regarding land disputes and development projects, leading to the loss of vital resources that sustain their livelihoods. This research demonstrates that these women bear an additional burden of domestic responsibilities, which are largely unrecognised, while also being marginalised in the socio-political and legal spheres. Through an intersectional lens, this study unveils the complex interactions of gender, ethnicity, and class, which create distinct forms of oppression, complicating the struggle of indigenous women to protect their land and culture. These conflicts are not simply issuing of agriculture; they represent a broader fight for recognition, autonomy, and the protection of ecosystems. In conclusion, the legal and policy frameworks often fail to adequately address the rights of indigenous women, highlighting the need for inclusive policies that ensure their participation in decision-making processes. It argues for the recognition of their ecological knowledge and cultural heritage in addressing and resolving land conflicts.